Generalised pustular psoriasis – a case report and review of therapeutic approaches - Osmola-Mańkowska, Agnieszka (Dermatology Review/Przegląd Dermatologiczny, 2014)
Introduction. Generalised pustular psoriasis (GPP) is regarded as a rare clinical subtype of psoriasis. The severity of GPP varies from a benign, chronic course to severe and widespread, life-threatening disease. Due to the uncommon nature of GPP, establishing treatment guidelines for this variant of psoriasis is challenging. Objective. To present the case of a patient with GPP with a short review of therapeutic approaches. Case report. Our patient was treated with standard methods such as acitretin, then cyclosporine and methotrexate as well as with biologic drug – infliximab. During the last and the most severe flare, combination therapy with systemic retinoid and PUVA (Re-PUVA) was used. Conclusions. The treatment in GPP should be determined individually according to the severity of the disease, age, gender and comorbidities, as well as according to the physician’s experience with particular methods and their side effects. In addition, the availability of therapeutic options should be taken into consideration.